DAMPAK PSIKOSOSIAL PENDERITA KUSTA DALAM PROSES PENYEMBUHANNYA - Nur Alam Fajar (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Leprosy remains a health problem in Indonesia that has complicated impact. It results in a highly complicated impact which is not only on medical aspect, but also in other aspects such as social, economic, culture, and national defense and security3. Till now, leprosy has been considered as a frightening disease by some patients including their family and even by small number of healthcare staffs. That problems are often assumed as causing factors for physical and social disorders because of the morbidity (as concomitant) and tendency seem to be more dominant than its medical problem. This is supported by a survey conducted in South Sulawesi, East Java, and West Java that states there is wrong sociocultural understanding about leprosy which still develops in society, such as leprosy as a genetic and witchery disease, a curse from God, a result of wrong choice of food, very contagious disease, and untreatable an uncurable diseases11. The sociocultural impacts have caused an excessive fear (leprophobia). With leprophobia and negative stigma, patients tend to be isolated from social interaction and they are not treatedhumanely7. The aim of this paper is to give an understanding to all parties concerned of the importance of psychosocial aspects experienced by leprosy patients in order to overcome and prevent the disease in the community. In this paper, a theoretical exploration of the methodology were used to provide a basic understanding about the progress of efforts to eliminate (leprophobia) in thecommunity through a psychosocial approach in our environments.